Çevresel etki değerlendirmesi ve Türkiye uygulaması - Yaş, Hakan (My University, 2005)
Çevresel etki değerlendirmesi önceleri fayda - maliyet analizinin bir parçasıydı. Ancak daha sonra, fayda maliyet analizi çevresel etki değerlendirmesinin bir parçası haline gelmiştir. Çıkış noktası ABD olan çevresel etki değerlendirmesi sürdürülebilir kalkınmanın ve çevre politikalarının uygulama araçlarından biridir. Uluslar arası örgütler nezdinde yapılan pek çok toplantılarla sürdürülebilir kalkınma bağlamında çevre politikaları belirlenmiş ve bunların uygulama araçlarından birinin de çevresel etki değerlendirmesi olduğu belirtilmiştir. Environmental impact assessment was formerly a part of cost - benefit analysis. Later, cost - benefit analysis has become a part of environmental impact assessment. Environmental impact assessment of which origin is USA is one of the implementation tool of both sustainable development and environmental politics. Environmental politics have been determined in the context of sustainable development with many meetings gathered by international organisations and hereby these meetings it has been stated that one of the implementation tool of those politics is environmental impact assessment. Environmental impact assessment has been able to come into force late by reason of rapid development. Turkey, who is in the European Union membership process, also comply with EU environmental impact assessment legislation. In this context, the Directives of European Union legislation on environmental impact assessment, in this thesis, have been given ex-ante the implementation in Turkey. Turkey has complied with European Union requirements on environmental impact assessment.
Keywords: Çevresel Etki Değerlendirmesi; Kamu yönetimi; Yerel Yönetimler; Yerel yönetimler (Belediyeler)